2006
DOI: 10.1007/s00775-006-0191-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlating EPR and X-ray structural analysis of arsenite-inhibited forms of aldehyde oxidoreductase

Abstract: Two arsenite-inhibited forms of each of the aldehyde oxidoreductases from Desulfovibrio gigas and Desulfovibrio desulfuricans have been studied by X-ray crystallography and electron paramagnetic resonance (EPR) spectroscopy. The molybdenum site of these enzymes shows a distorted square-pyramidal geometry in which two ligands, a hydroxyl/water molecule (the catalytic labile site) and a sulfido ligand, have been shown to be essential for catalysis. Arsenite addition to active as-prepared enzyme or to a reduced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 43 publications
5
21
0
Order By: Relevance
“…X-ray studies show that both alcohol molecules are stabilized in their respective positions by a hydrogen bond with the O atom from Glu869 (see Figure 3). A similar feature was also observed for the arsenite moiety in the structure of arsenite-inhibited DgAOR 7,8 and for substrates in closely related proteins. 5,13 Additional proof of the stability of the Mo-alcohol adducts is given by the fact that inhibitor molecules cannot be easily removed once they entered into the active site pocket, as indicated by the extensive washing necessary for the enzyme to regain activity.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…X-ray studies show that both alcohol molecules are stabilized in their respective positions by a hydrogen bond with the O atom from Glu869 (see Figure 3). A similar feature was also observed for the arsenite moiety in the structure of arsenite-inhibited DgAOR 7,8 and for substrates in closely related proteins. 5,13 Additional proof of the stability of the Mo-alcohol adducts is given by the fact that inhibitor molecules cannot be easily removed once they entered into the active site pocket, as indicated by the extensive washing necessary for the enzyme to regain activity.…”
Section: Discussionsupporting
confidence: 73%
“…This indicates that either oxidized Mo(VI) or reduced Mo(IV) forms can react with the alcohol molecules, similar to what occurs for arsenite inhibition. 8 ENDOR studies of normal and deuterated EDOtreated XO detected a hyperfine coupling of 3.6 MHz (∼1.2 G) that was assigned to the protons of the CH 2 groups, confirming that the ethylene glycol is coordinated to Mo in the EPR-active species. 52 On the basis of this result, it was suggested that the Mo(V) ion is coordinated through both oxygen atoms of the alcohol moiety.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…For biological systems, the evaluation of J is not only relevant to understand the electronic properties of the redox centers, but also to learn on structural and functional aspects of the systems that complement information obtained from conventional structural and kinetic techniques [18][19][20]. Particularly, the analysis of the magnetic interaction between centers can be advantageously used to determine intercenter distances, to assign the EPR active centers with those of the structure, and to study the integrity of the electron transfer pathways in distinct protein conditions [21][22][23][24][25][26]. Additional interest in the evaluation of exchange interactions is that the rate of electron transfer through a chemical path linking two paramagnetic centers is proportional to |J| under conditions of maximal rate, which means that the value of |J| can be advantageously used to predict the ability of the chemical path as electron transfer conduit [23].…”
Section: Introductionmentioning
confidence: 99%